First record of a Basking Shark Cetorhinus maximus (Gunnerus, 1765) in the Brazilian Atlantic - Sadowsky, Victor (1973)
The capture on November 19, 1970, of a juvenile female of the Basking Shark Cetorhinus maximus (Gunnerus, 1765), 438 cm long, is the first record of this species in the Brazilian Atlantic, at about 24º00' to 24º10' Lat. S, and 45º35' to 45º15' Long- W. The teeth are mostly in three, sometimes two or four, functional series. Vertebral numbers and characteristics: Precaudal - 53; Caudal - 56; Total - 109; Monospondylous - 37; A-values - 167; B-values - 82 (sensu Springer & Garrick, 1964). The gill rakers are well developed and brilliant black.